Deepening relations between Ukraine and EU in the context of DCFTA conditions. (Economics and region, 2019)
The article is devoted to the study of the real state and consequences of deepening of economic cooperation between Ukraine and the EU in the conditions of implementation of the Association Agreement. The state of implementation of the Association Agreement between Ukraine and the European Union is considered on the basis of the study of official government reports and the results of independent experts' studies. The analysis of the current state, structure, tendencies and peculiarities of trade cooperation of Ukraine with the countries of the European Union is conducted. The influence of the Deep and Comprehensive Free Trade Area with the EU is determined. Particular attention is paid to the problems of Ukrainian companies entering the EU market and the use of duty-free tariff quotas.
Keywords: European integration; European Union; Association Agreement; Free Trade Area; export; import